The revolving door, state connections, and inequality of influence in the financial sector. Issue 4 (18th January 2019) - Brezis, Elise S.; Cariolle, Joël
Abstract: This paper shows that the revolving door generates inequality of influence between financial firms and creates economic distortions. We first develop a theoretical model, introducing the notion of "bureaucratic capital" and stressing how the revolving door generates inequality in bureaucratic capital leading to inequality in profits. Then this prediction is tested, using a new database that tracks the revolving door process involving the 20 biggest US "diversified banks." We show that regulators who supply a large stock of bureaucratic capital are more likely to be hired by the top five banks. We also develop indices of the inequality of influence between banks. We show that banks in the top revenue quintile concentrate around 80% of revolving door movements. Goldman Sachs appears as the prime beneficiary of this process, capturing approximately 30% of the total stock of bureaucratic capital.